Pesan Komunikasi Islam Dalam Korelasi Moralitas Manusia Dan Bencana Alam Di Nusantara - Alen Manggola (Al-MUNZIR, 2022)
The purpose of this study is to find out and analyze Islamic views based on the causes of natural disasters in Indonesia. The research results show that most of the causes of natural disasters are immorality and polytheism. In line with QS. Surah Ar-Rum verses 41-42 that natural disasters are the work of human hands themselves and also shirk towards Allah. Thus it can be understood that natural disasters are not only caused by the aging of a nature. Getting closer and repenting is the only solution that can be taken while a human being is still alive. So by getting closer to the creator and cultivating justice and love for the environment, it will give change to nature and calm the people from the fear of natural disasters. Keywords: Islamic communication, Bencana Alam, surah ar-Rum 41-42